Loss of Gut Microbiota Alters Immune System Composition and Cripples Postinfarction Cardiac Repair - Tang, Tony W H; Chen, Hung-Chih; Chen, Chen-Yun; Yen, Christopher Y T; Lin, Chen-Ju; Prajnamitra, Ray P; Chen, Li-Lun; Ruan, Shu-Chian; Lin, Jen-Hao; Lin, Po-Ju; Lu, Hsueh-Han; Kuo, Chiung-Wen; et al. (Circulation (New York, N.Y.), 2019)
The impact of gut microbiota on the regulation of host physiology has recently garnered considerable attention, particularly in key areas such as the immune system and metabolism. These areas are also crucial for the pathophysiology of and repair after myocardial infarction (MI). However, the role of the gut microbiota in the context of MI remains to be fully elucidated. To investigate the effects of gut microbiota on cardiac repair after MI, C57BL/6J mice were treated with antibiotics 7 days before MI to deplete mouse gut microbiota. Flow cytometry was applied to examine the changes in immune cell composition in the heart. 16S rDNA sequencing was conducted as a readout for changes in gut microbial composition. Short-chain fatty acid (SCFA) species altered after antibiotic treatment were identified by high-performance liquid chromatography. Fecal reconstitution, transplantation of monocytes, or dietary SCFA or Lactobacillus probiotic supplementation was conducted to evaluate the cardioprotective effects of microbiota on the mice after MI. Antibiotic-treated mice displayed drastic, dose-dependent mortality after MI. We observed an association between the gut microbiota depletion and significant reductions in the proportion of myeloid cells and SCFAs, more specifically acetate, butyrate, and propionate. Infiltration of CX3CR1+ monocytes to the peri-infarct zone after MI was also reduced, suggesting impairment of repair after MI. Accordingly, the physiological status and survival of mice were significantly improved after fecal reconstitution, transplantation of monocytes, or dietary SCFA supplementation. MI was associated with a reorganization of the gut microbial community such as a reduction in Lactobacillus. Supplementing antibiotic-treated mice with a Lactobacillus probiotic before MI restored myeloid cell proportions, yielded cardioprotective effects, and shifted the balance of SCFAs toward propionate. Gut microbiota-derived SCFAs play an important role in maintaining host immune composition and repair capacity after MI. This suggests that manipulation of these elements may provide opportunities to modulate pathological outcome after MI and indeed human health and disease as a whole.